2016
DOI: 10.1038/bjc.2016.151
|View full text |Cite
|
Sign up to set email alerts
|

A circulating miRNA assay as a first-line test for prostate cancer screening

Abstract: Background:Prostate cancer (PCa) screening currently relies on prostate-specific antigen (PSA) testing and digital rectal examination. However, recent large-scale studies have questioned the long-term efficacy of these tests, and biomarkers that accurately identify PCa are needed.Methods:We analysed the levels of circulating microRNAs (miRNAs) in patients with elevated PSA who were diagnosed with either localised PCa (n=36) or benign prostatic hyperplasia (BPH, n=31) upon biopsy. Real-time RT–PCR with Taqman p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 17 publications
1
48
0
1
Order By: Relevance
“…In our PCa patient cohort, we found that miR‐221, miR‐425, miR‐494, miR‐361 and miR‐130b were the most upregulated plasma miRNAs. With the exception of miR‐425, miR‐494 and miR‐361, the deregulation of miR‐221 and miR‐130b in the plasma of PCa patient has already been described . Agaoglu et al .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In our PCa patient cohort, we found that miR‐221, miR‐425, miR‐494, miR‐361 and miR‐130b were the most upregulated plasma miRNAs. With the exception of miR‐425, miR‐494 and miR‐361, the deregulation of miR‐221 and miR‐130b in the plasma of PCa patient has already been described . Agaoglu et al .…”
Section: Discussionmentioning
confidence: 98%
“…In addition, Sharova et al . calculated the ratio of the plasma levels of circulating miR‐106a and miR‐130b in PCa patients, and found that it predicts the presence of localized PCa …”
Section: Discussionmentioning
confidence: 99%
“…Sharova et al . found that the ratios between three circulating miRNAs could better discriminate prostate cancer from benign prostate hyperplasia than prostate‐specific antigen (PSA) values in 67 patients . In a recent study, the performance of several noninvasive biomarkers (PSA, androgen receptor CAG repeat analysis and promoter methylation analysis of the genes GSTP1 and RASSF1A) was investigated in plasma from 186 men scheduled for biopsy due to elevated PSA levels and/or abnormal digital examination findings.…”
Section: Can Ctdna Be Used To Distinguish Benign From Malignant Lesions?mentioning
confidence: 99%
“…Deregulated miRNAs commonly occur in many cancers and different miRNAs have been proposed as promising diagnostic biomarkers in many cancers, including MM. In general miRNAs are excellent biomarkers because are stable and can be analyzed in routinely processed tissue samples (87), as well as in blood samples (88,89).…”
Section: Micrornas (Mirnas)mentioning
confidence: 99%